Schizophyllum commune : An unexploited source for lignocellulose degrading enzymes - Tovar Herrera, Omar Eduardo; Martha Paz, Adriana Mayrel; Pérez LLano, Yordanis; Aranda, Elisabet; Tacoronte Morales, Juan Enrique; Pedroso Cabrera, María Teresa; Arévalo Niño, Katiushka; Folch Mallol, Jorge Luis; Batista García, Ramón Alberto (2018)
Abstract Lignocellulose represents the most abundant source of carbon in the Earth. Thus, fraction technology of the biomass turns up as an emerging technology for the development of biorefineries. Saccharification and fermentation processes require the formulation of enzymatic cocktails or the development of microorganisms (naturally or genetically modified) with the appropriate toolbox to produce a cost- effective fermentation technology. Therefore, the search for microorganisms capable of developing effective cellulose hydrolysis represents one of the main challenges in this era. Schizophyllum commune is an edible agarical with a great capability to secrete a myriad of hydrolytic enzymes such as xylanases and endoglucanases that are expressed in a high range of substrates. In addition, a large number of protein- coding genes for glycoside hydrolases, oxidoreductases like laccases (Lacs; EC 1.10.3.2), as well as some sequences encoding for lytic polysaccharide monooxygenases (LPMOs) and expansins- like proteins demonstrate the potential of this fungus to be applied in different biotechnological process. In this review, we focus on the enzymatic toolbox of S. commune at the genetic, transcriptomic, and proteomic level, as well as the requirements to be employed for fermentable sugars production in biorefineries. At the end the trend of its use in patent registration is also reviewed. KEYWORDS biorefinery, biotechnology, lignocellulolytic enzymes, lignocellulose, Schizophyllum commune